2015
DOI: 10.3390/en8042548
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies and Advancements in the Calibration of Building Energy Models

Abstract: Buildings do not usually perform during operation as well as predicted during the design stage. Disagreement between simulated and metered energy consumption represents a common issue in building simulation. For this reason, the calibration of building simulation models is of growing interest. Sensitivity and uncertainty analyses play an important role in building model accuracy. They can be used to identify the building model parameters most influent on the energy consumption. Given this, these analyses shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 71 publications
0
110
0
1
Order By: Relevance
“…Disagreement between simulated and metered energy consumption represents a common issue in building simulation [16]. When dealing with existing buildings, models are usually calibrated in order to obtain low values of the Coefficient of Variation of Root Mean Squared Error (CV (RMSE)) and of Normalized Mean Bias Error (NMBE) for the whole building's monthly use [17,18].…”
Section: Uncertainty Evaluationmentioning
confidence: 99%
“…Disagreement between simulated and metered energy consumption represents a common issue in building simulation [16]. When dealing with existing buildings, models are usually calibrated in order to obtain low values of the Coefficient of Variation of Root Mean Squared Error (CV (RMSE)) and of Normalized Mean Bias Error (NMBE) for the whole building's monthly use [17,18].…”
Section: Uncertainty Evaluationmentioning
confidence: 99%
“…In most studies, simulations are validated for idealized cases, which means that there are differences between the simulation program and the actual energy use of the building. This results from the fact that most existing buildings do not operate as well as they were designed to operate [10][11][12]. Thus, the building model should be adjusted by tuning the input values to match the current energy demands.…”
Section: Introductionmentioning
confidence: 98%
“…A detailed review of the calibration techniques for building simulation can be found elsewhere (Coakley et al 2014;Fabrizio and Monetti 2015). The calibration can be conducted with either deterministic or probabilistic method.…”
Section: Stochastic Building Energy Models For Individual Buildingsmentioning
confidence: 99%